Civil Liability of Influencers for Product Endorsements That Harm Consumers - Hassanah, Hetty; Fahira, Audy; Permatasari, Shaylah Windi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
With the development of digital marketing, influencers now become influential actors in promoting products through social media. In the context of increasing endorses for illegal, dangerous, and even misleading products, it becomes important to explore the legal issues relating to civil liability when consumers lose money. The purpose of this research is to determine the legal standing of influencers and the grounds for civil liability for misleading product endorsement which leads to consumer loss. In order to achieve the objective, this paper tries to analyzethe legal standing of influencers and how the misleading act during endorsement can be considered as unlawful acts according to civil liability principle. The method employed here is descriptive analytical approach by using normative juridical method. The findings show that influencers may be subjected to civil liability if the endorse act contains misleading content, no transparency and causes the consumers to suffer any loss.